2019
DOI: 10.21203/rs.2.461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Nature stroke study; NASTRU - A randomised controlled trial of nature-based post-stroke fatigue rehabilitation

Abstract: Fatigue is common after stroke and contributes to disability and impaired quality of life. Currently, there is insufficient evidence on the efficacy of any intervention for post-stroke fatigue. The aim of the study was to examine whether 10 weeks Nature-based rehabilitation (NRB) as add-on to standard care may improve post-stroke fatigue, perceived value of everyday occupations, function, activity and participation compared to standard care only (Clinical Trial.gov Identifier: NCT02435043, 2012/352, 05-06-2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…After screening titles, 10,252 were excluded and seven studies remained for full text reading (Figure 1). Only two articles and a conference abstract paper were found via database search (Thomas 2004;Walker et al 2005;Palsdottir 2017), while three experimental studies (Kim M-Y et al 2010;Ho et al 2016) and a qualitative study (Barello et al 2016) were found by hand search and obtained via Google Scholar. All of these, except the conference paper, were included, and further two possible records were found in a systematic review (Kamioka et al 2014) and Google Scholar but were excluded as they only had full text in Korean or published as conference abstracts (Palsdottir 2017).…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles, 10,252 were excluded and seven studies remained for full text reading (Figure 1). Only two articles and a conference abstract paper were found via database search (Thomas 2004;Walker et al 2005;Palsdottir 2017), while three experimental studies (Kim M-Y et al 2010;Ho et al 2016) and a qualitative study (Barello et al 2016) were found by hand search and obtained via Google Scholar. All of these, except the conference paper, were included, and further two possible records were found in a systematic review (Kamioka et al 2014) and Google Scholar but were excluded as they only had full text in Korean or published as conference abstracts (Palsdottir 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Some HT studies have implemented SNOSE (e.g. Palsdottir et al, 2020). The process involves a rigorous methodology and article publication interpretation process that includes an explanation of security measures, and who prepared and opened the envelopes (Clark et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions drew on CBT and/or elements of CBT: Cognitive restructuring and problem-solving were used by Nguyen et al (2019), included in the cognitive treatment component of the COGRAT intervention in Zedlitz et al (2012), and in the emotional regulation component used by Stubberud et al (2019). Although MBSR was one of the three categories, elements of mindfulness were also used in other interventions, including the multicomponent interventions used by Stubberud et al (2019) and Pálsdóttir et al (2020). Other commonalities across interventions included tailoring strategies to individual participants such that they could be implemented in participants’ daily routines, and the use of homework tasks (e.g., home strategy practice) and assignments (e.g., maintaining a fatigue diary).…”
Section: Discussionmentioning
confidence: 99%
“…A third study in the multicomponent intervention group investigated a nature-based rehabilitation (NBR) program on PSF (Pálsdóttir et al, 2020). The intervention group underwent standard care in addition to NBR, which was grounded in horticultural therapy, supported by a multimodal rehabilitation team that utilized nature for multisensory stimulation for physical, emotional, and cognitive stimulation.…”
Section: Multicomponent Interventionsmentioning
confidence: 99%